The impact of attachment security on death preparation in advanced cancer: The role of couple communication. Issue 5 (26th February 2020) - Mah, Kenneth; Shapiro, Gilla K.; Hales, Sarah; Rydall, Anne; Malfitano, Carmine; An, Ekaterina; Nissim, Rinat; Li, Madeline; Zimmermann, Camilla; Rodin, Gary
Abstract: Objective: Attachment security protects psychological well‐being in patients with advanced cancer, but its effect on death preparation in this population has not been demonstrated. We examined the relationship of attachment security to death preparation in advanced cancer and tested whether couple communication mediates this relationship and whether gender and age moderate this mediating effect, using longitudinal data from a psychotherapy trial. Methods: Patients with advanced cancer who lived with a partner ( N baseline = 289) completed measures of attachment security (attachment avoidance, attachment anxiety), couple communication, and death preparation (preparation for end of life, life completion) and attendant health involvement (relationship with healthcare provider). A moderated mediation model was evaluated at each time period (baseline, 3 months, and 6 months). Results: Couple communication mediated the relationship of attachment security to preparation for end of life and life completion ( b 's = −.06 to −.10). Anxiety × Gender effects on baseline couple communication ( P 's = .016) indicated that women with greater attachment anxiety reported worse communication than their male counterparts. Couple‐communication × Gender × Age effects on baseline preparation for end of life ( P = .007‐.020) suggested that women showed better preparation with better couple communication. Younger patients reported less preparation than older patients, especially with poorer communication, but their preparation increased with better communication, especially in younger men. Conclusions: Attachment security supports death preparation in advanced cancer partly through better couple communication. Couple‐based psychotherapeutic interventions, especially for younger individuals and women with attachment anxiety, may facilitate constructive conversations and death preparation.